Envolvimento dos receptores opióides e receptores a-2-adrenérgicos no efeito gastroprotetor da lectina de sementes de abelmoschus esculentus em camundongos - Ribeiro, Kátia Alves (2014)
The use of plants as sources of new drugs has been widely used by pharmaceutical industry. Lectins are proteins that recognize specific sites in the molecules and bind reversibly to carbohydrates without altering the covalent structure of the glycosidic sites. They are distributed in a wide variety of plant species having in greater amount in grain legumes and grasses. Abelmoschus esculentus (AEL ) is an vegetable belonging to the Malvaceae family, popularly known as okra, exhibiting anti-inflammatory, antinociceptive and anticoagulant effects. The aim of this study was to investigate the gastroprotective effect of lectin from seeds of AEL using a model of absolute ethanolinduced gastric lesion in mice and its mechanisms of action were also studied. After fasting for 24 h, male Swiss mice (25-30g) received intravenously (i.v.) AEL (0.01, 0.1 or 1 mg/kg) 30 min before administration (per os) of absolute ethanol (0.2 ml/animal). Groups treated with vehicle (saline) or ranitidine (80 mg/kg, p.o.) were used as negative and positive controls, respectively. After 30 min, animals were euthanized under anesthesia, and the stomachs removed, opened in the long curvature and examined grossly and histologically (H & E). In another series of experiments to investigate the mechanisms of action of AEL, groups were pretreated with: (1) naloxone (nonselective opioid antagonist) and morphine (agonist receptors); (2) misoprostol (prostaglandin E1 analogue) and indomethacin (non-selective COX inhibitor); (3) L- NAME (nonselective NOS inhibitor) and L- arginine (the substrate of NOS); and (4) clonidine (α-2- adrenergic agonist) and yohimbine (α-2-adrenoceptor selective antagonist). AEL has gastroprotective effect that appears to involve the activation of α-2-adrenergic receptors and opioid receptors, but does not depend on prostaglandins and nitric oxide.